Strengthening Students' Religious Character Through The Use Of Youtube Social Media Religious Content, Student Boarding School And Al-Qur'an Memorization - Euis Komala; Tedi Priatna; Bambang Samsul Arifin; Mohammad Erihadiana (Yayasan Azka Hafidz Maulana, 2026)
This study aims to identify and describe the objectives, programs, processes, supporting and inhibiting factors, evaluation, and impact of strengthening students' religious character through YouTube religious content, student Islamic boarding schools, and Al-Qur'an memorization at both institutions. The study uses a qualitative approach with a comparative case study method. Data collection via participatory observation, in-depth interviews, and documentation studies. Inductive analysis through reduction, data presentation, and drawing conclusions for in-depth findings. The results of the study indicate that the process is through routine habits, reflection, and internalization of Islamic values ​​​​in campus activities. Supporting factors include leadership support, lecturer competence, student participation, and a conducive environment. Inhibiting factors include technological limitations, variations in student backgrounds, content supervision, globalization. The impact of strengthening students' religious character using social media, YouTube religious content, student Islamic boarding schools, and Al-Qur'an memorization is an increase in worship discipline, patience, empathy, and the practice of Islamic values ​​​​in academic-social life.